Widely Tunable Electro-Absorption Modulated V-Cavity Laser - Sen Zhang; Yimin Xia; Jianjun Meng; Jiasheng Zhao; Jian-Jun He (IEEE Photonics Journal, 2019)
We report a widely tunable V-cavity laser monolithically integrated with an electro-absorption modulator (EAM). The device shows a 41-nm wavelength tunability covering 51 channels at 100 GHz spacing on the ITU grid, with a side-mode suppression ratio (SMSR) higher than 47 dB. Error-free transmission over 50 km standard single-mode fiber at 10 Gb/s is demonstrated at all wavelengths over the tuning range. The integrated EAM exhibits a dynamic extinction ratio higher than 12.5 dB. The bit-error-rate measurements show a power penalty less than 3 dB for 50-km transmission. The results demonstrate that this ultra-compact and regrowth-free electro-absorption modulated tunable laser can be a cost-effective transmitter solution for DWDM metropolitan and access networks.